THE FEATURES OF METHODOLOGY FOR PHARMACOECONOMICS ANALYSIS OF VACCINATION - A. Yu. Kulikov; Yu. L. Akimova (IRBIS LLC, 2015)
In this paper gradually showed features of the methodology for conducting of pharmacoeconomics analysis of vaccination. Discribes criteria of selection of performance indicators for various vaccines. We performed accounts of costs associated with vaccination and also accounts and analysis of performance indicators